Archival data on wild food plants used in Poland in 1948 - Łuczaj Łukasz (BMC, 2008)
Abstract Background In 1948, Professor Józef Gajek initiated a detailed census of the wild edible plants used in Poland. The questionnaires were collected by correspondents of the Polish Folklore Society in 95 localities throughout Poland. A major part of these archival materials, including a substantial collection of herbarium specimens, had not undergone thorough analysis prior to this study, which presents a quantitative analysis of this archival set of data. Methods Herbarium specimens were identified and a database was created. Results Ninety-eight taxa identified to genus or species level, including 71 botanical species, identified using herbarium specimens, were found. On average only 11 edible plant species per locality were listed, the longest list included 39 species. No correlation between latitude and the number of edible species was found, whereas there was small but significant correlation with the longitude. Fruits were the most frequently collected part of plants. Most plants were primarily collected by women and children. Children both helped parents to collect wild fruits and also ate many species raw, which were not consumed by adults, but had often been eaten in the past. Eighteen of the taxa had not been reported in a recent comprehensive review of edible plants of Poland. Stratiotes aloides, used as a famine vegetable in the Łódź region, has never been reported as edible in any ethnobotanical literature. Conclusion The results undermine the conclusions of a recent comprehensive review of edible plants of Poland, which stated that many more wild edible plants have been collected in the Carpathians than in lowland Poland. However such results were shown to be caused by the substantially larger number of ethnographic studies undertaken in the Carpathians. In fact, large numbers of edible plant species were collected in the mid-20th century in a few regions, particularly along the eastern border, in the Carpathians and in communities originating from the expanded Soviet Union, which had been resettled to the north-west of Poland in 1945.